Studi Bibliometrix Vosviewers dan Literature Review of Scopus 2020-2025 - Davita Dewardani; Della Widya Ayu; Puji Wahono; Indra Pahala (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to map the progress of studies on the impact of tax avoidance using a bibliometric approach with the help of VOSviewer software and a literature review from the Scopus database for the period 2020–2025. The analysis was conducted on relevant scientific publications to identify research trends, dominant keywords, collaboration between authors, and the most influential journals and institutions in this topic. The results of the study show a significant increase in the number of publications related to the topic of tax avoidance impact, with a primary focus on issues such as corporate governance, financial performance, and transparency. In addition, it was found that studies on the impact of tax avoidance increasingly involve cross-disciplinary approaches and international collaboration. These findings provide a comprehensive overview of the direction of impact tax avoidance research and can be a strategic reference for academics and policymakers in understanding the implications of tax avoidance practices on the public and private sectors.